PENGARUH MOTIVASI KERJA, KOMPETENSI KERJA DAN PENGENDALIAN INTERN TERHADAP KINERJA PEGAWAI SATUAN KERJA PERANGKAT DAERAH KOTA PARIAMAN - Emil Regina Fransiska; Restu Agusti; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of work motivation, competence performance, and internal control of the performance of employees in the regional work units of Pariaman. The research was conducted on the regional work units ofPariaman.The population in this study were employees who work in the regional work units of Pariaman. Sampling technique used was purposive sampling. Respondents in this study is the Head of SKPD, Secretary of SKPD, Head of Sub Division of Finance, and Chief Financial administrator. The sample used in this study were 76 respondents. The statistical method used to test the hypothesis of the research is multiple linear regression analysis using SPSS software version 21.0The results showed that the variables of work motivation, work competency, and internal control influence on employee performance SKPD of Pariaman.Keywords: Work motivation, competence performance, and internal control, and performance of employees in the regional work.